Letter
021-0071-001 3, Victoria Street (4th Floor) London S.W.1. GENERALITAT DE CATALUNYA COMISSARIAT D'INFORMACIO A L'ESTRANGER Spanish People's Front Abbey 4857 " 5123 9th March, 1937 W. Henderson Esq., Transport House, London. phoned reply to effect that workers can be admitted without delegation credentials. HT Dear Sir, My secretary asked this morning if it would be possible for me to attend the Congress tomorrow, Thursday and Friday. He was told that it will be private, except, of course, the meeting. If it were possible, however, I should greatly appreciate any facilities you could give me, as I realise the very great importance of this Congress to the Spanish and Catalan Trades Unions, to whom I am responsible. I have not mentioned this to Mr. Gillies, as I thought possibly you would be dealing with it. Yours sincerely, D.R. Darling Propaganda Commissariat. Generalitat de Catalunya. 292/946/21/71